1977
DOI: 10.1007/bf01003627
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical studies of mucosubstances and lipids in normal human oesophageal epithelium

Abstract: The histochemistry of lipids and mucosubstances in normal human oesophageal epithelium were studied in biopsies obtained from 24 patients undergoing investigations of the upper gastro-intestinal tract. Neutral fat droplets, 1-2 mum in diameter, were present in all layers, the greatest number being in the functional layer cells. No unsaturated lipids or fatty acids were demonstrable. Much glycogen was present in the cytoplasm of the prickle and functional cell layers as demonstrated by PAS (and diastase digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…This optical filtering effect has also been observed in autofluorescence spectroscopy of gastric and esophageal neoplastic tissues as a result of the increased epithelial proliferation. 23,24,42 It is particularly interesting that we observed inverse linear relationship (correlation coefficient R > 0.92) between collagen and triolein in the esophagus, suggesting that the large interpatient variation in the lipids signals could be connected with epithelial properties (e.g., thickness, lipid content) 40,41 within the esophagus. To further evaluate the clinical implications of interorgan variability, we also employed a powerful classification algorithm [e.g., partial least squares-discriminant analysis (PLS-DA)] 25 to exploit subtle spectral variations of the entire Raman spectra that are not resolved by biomolecular modeling.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This optical filtering effect has also been observed in autofluorescence spectroscopy of gastric and esophageal neoplastic tissues as a result of the increased epithelial proliferation. 23,24,42 It is particularly interesting that we observed inverse linear relationship (correlation coefficient R > 0.92) between collagen and triolein in the esophagus, suggesting that the large interpatient variation in the lipids signals could be connected with epithelial properties (e.g., thickness, lipid content) 40,41 within the esophagus. To further evaluate the clinical implications of interorgan variability, we also employed a powerful classification algorithm [e.g., partial least squares-discriminant analysis (PLS-DA)] 25 to exploit subtle spectral variations of the entire Raman spectra that are not resolved by biomolecular modeling.…”
Section: Discussionmentioning
confidence: 94%
“…The biochemical modeling indicates a considerably elevated content in lipids of the distal esophagus as compared to the gastric cardia (p = 3.2×10 −6 ), which is in agreement with the reports on accumulations of lipids in the dense cell layers of the esophageal epithelium, as a part of the mucosal barrier. 40,41 Further, the relative less collagen of the esophagus compared to gastric is also linked with the thick squamous epithelium obscuring the Raman signal from the extensive connective tissues in the lamina propria. This optical filtering effect has also been observed in autofluorescence spectroscopy of gastric and esophageal neoplastic tissues as a result of the increased epithelial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen, which is absent only from the basal cells (Hopwood et al, 1977), was demonstrated by the PAS technique (Pearse, 1968). This technique usefully divides the epithelium into two compartments which may then be assessed histochemically.…”
Section: Patientsmentioning
confidence: 99%
“…5) [7]. Similar glycoconjugates have been found within the inter cellular spaces of the human esophagus [9]. Although tight junctions are extremely important in other tissues, studies suggest that they may be less important in esophagus [7], However, being the most narrow region between adjacent cells, tight junctions may help retain the presumed largersized giycoconjugate material within the intercellular space.…”
mentioning
confidence: 75%